DAMPAK PEMBERIAN KURMA SEGAR (PHOENIX DACTYLIFERA) TERHADAP KADAR HEMOGLOBIN IBU NIFAS - Berliana Irianti; Nur Israyati; Nelly Karlinah (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The maternal Death Rate is one marker to see the outcome of maternal well-being endeavors. Bleeding is a factor in maternal mortality. Anemia in pregnant women can result in bleeding during childbirth. Anemia during pregnancy and blood loss during childbirth influence iron deficiency anemia during the puerperium. The study's objective was to ascertain whether giving birth to mothers who had recently given birth increased their levels of hemoglobin (Hb). Pre-experimental research employs pretest and posttest designs for a single group. The review was conducted between June and July 2022. Purposive sampling was used to select 17 respondents for this study's sample. An observation sheet for the hemoglobin level was used in the research instrument. Analysis of data with and without bivariates According to the univariate results, up to 13 participants had generally low hemoglobin levels before the administration of date juice, i.e., 76.5%. A p-value of 0.002 was reported for bivariate results using the Wilcoxon rank sum test. This suggests that date juice for women after childbirth increases hemoglobin (Hb) levels. It is believed that in the future, after childbirth, women can eat dates to increase the level of hemoglobin (hemoglobin).